SOM FAIR 2016: BRIDGING RELATIONSHIP BETWEEN USM STUDENTS AND THE COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, March 2016 The Universiti Sains Malaysia (USM) School of Management (SOM) Fair 2016 that was recently held at the USM Convocation site has become a platform to strengthen the relationship among USM students.